(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article investigates the evolution of home craftsmanship from prehistoric times through the early modern era, focusing on the transition from basic survival implements to complex domestic artifacts. It examines the social, economic, and cultural factors that influenced craftsmanship practices across different historical contexts. The study highlights the significance of craftsmanship in shaping community identity and its transformation during industrialization. Additionally, it discusses contemporary revivals of interest in traditional craftsmanship and the implications for cultural heritage preservation.